Goodness-of-fit test for hazard rate. Issue 2 (2nd April 2020) - Vital, Ralph-Antoine; Patil, Prakash
ABSTRACT: In Pharmacokinetic (PK) and Pharmacodynamic (PD), the hazard rate functions play a central role in modelling time-to-event data. In the context of assessing the appropriateness of a given parametric hazard model, Huh, Y., and Hutmacher, M. [(2016), 'Application of a Hazard-based Visual Predictive Check to Evaluate Parametric Hazard Models', Journal of Pharmacokinetics and Pharmacodynamics, 43, 57–71] showed that a hazard-based visual predictive check is as good as a visual predictive check based on the survival function. However, for the lack of objectivity of such a visual method in this paper, we propose a nonparametric goodness-of-fit test for hazard rate functions. Besides having good power properties against the fixed alternatives, the proposed nonparametric kernel-based test also can detect alternatives converging to the null at the rate of N β,   β < 1 / 2, where N is the sample size.